Clinical Management of Atypical Cases of Acute Myeloid Leukemia Associated with Polyuria-Polydipsia Syndrome : Array - Ciortea, Diana-Andreea; Elkan, Eva Maria; Doagă, Alexandra Mihaela; Matei , Madălina Nicoleta; Nechita, Aurel (Acta Universitatis Danubius. Œconomica, 2021)
Objectives Acute leukaemia is the most common type of cancer in the paediatric population and the myeloid form represents only 15 percent. In this paper we aim to emphasize the management difficulties of this pathology in pediatric patients. Prior Work Studies addressing the costs and burden of acute myeloid laeukemia (AML) in children are sparse in the international literature, due to the low incidence rate, high mortality and some rare clinical aspects, such as polyuria-polydipsia syndrome. Hematologic tests usually can be relevant. Less common complications, that may require urgent intervention, include central nervous system involvement, hyperleukocytosis, and tumor lysis syndrome. There for, the total amount of resources used for the management of these patients represent an important burden for the medical systems all over the world. Approach In the current paper we present two clinical cases of paediatric patients diagnosed with AML, associated with leukostasis syndrome, neurologic impairment. ResultsIn both cases it was more cost effective to use a rational corroboration of basic diagnostic tools adapted to each clinical form. Due to the fulminant evolution of these patients towards a negative outcome, we focused the most effort and resources on intensive care treatment methods to prolong the survival rate of our patients. Implications Such atypical cases may represent a strenuous management challenge for pediatric medical professionals and financial health system responsible. Value Clinical presenting aspects described in these two cases are extremely rare in pediatrics and represent an effective way to improve medical practice and share a local clinical management experience and resources usage.